Implementation of National Education Standards at MTs Anwaha - Nurul Maulida; Syahrani Syahrani; Rusidah Rusidah; Siti Rahmah; Sri Kamaliah (Horizons : Journal of Education and Social Humaniora, 2026)
This study aims to analyze the implementation of the National Education Standards at MTs Anwaha, focusing on the application of the eight national education standards, the integration of these standards without compromising the school’s unique characteristics, and the promotion of child friendly education. A qualitative approach with a case study design was employed, allowing for an in-depth exploration of institutional practices within a real-world context. Data were collected through in-depth interviews, observations, and documentation, involving the madrasah principal, teachers, educational staff, and students as informants. Data analysis was conducted using the Miles and Huberman model through the stages of reduction, presentation, and drawing conclusions. The research results indicate that MTs Anwaha has comprehensively and integrally implemented the eight National Education Standards in both teaching practices and madrasah management. Furthermore, the madrasah has successfully integrated the national standards without compromising its institutional distinctiveness rooted in Islamic values, as reflected in its religious culture and the character development of students. Additionally, the implementation of the National Education Standards is aligned with child-friendly education principles, evidenced by a safe, participatory, and humanistic learning environment. This study concludes that the success of SNP implementation is determined not only by compliance with standards but also by the madrasah’s ability to integrate institutional values and a child-friendly approach. The implications of this study underscore the importance of an integrative model in the development of holistic and sustainable madrasah education quality.